A fine white dust - Rylant, Cynthia (Bradbury Press, 1986)
The visit of the traveling Preacher Man to his small North Carolina town gives new impetus to thirteen-year-old Peter's struggle to reconcile his own deeply felt religious belief with the beliefs and non-beliefs of his family and friends.